2002
DOI: 10.14411/fp.2002.051
|View full text |Cite
|
Sign up to set email alerts
|

Trickle and single infection with Discocotyle sagittata (Monogenea: Polyopisthocotylea): effect of exposure mode on parasite abundance and development

Abstract: Abstract. Experimental infection of rainbow trout Oncorhynchus mykiss (Walbaum) with the monogenean Discocotyle sagittata (Leuckart, 1842) allowed comparison between trickle and single exposure, two infection modes demonstrated to occur in the wild. Both types of infection resulted in mean larval attachment success around 50%, which was significantly dependent on dose of infective larvae used (P < 0.0001), but was not affected by mode of infection (P = 0.244). Worms recovered from fish exposed to the same num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…However, their study also showed development to be affected by the number of larvae used and the mode of infection, i.e. whether single or trickle (multiple) exposure events (Rubio-Godoy and Tinsley, 2002). In contrast, development periods are known for a number of monopisthocotylean monogeneans.…”
Section: Discussionmentioning
confidence: 99%
“…However, their study also showed development to be affected by the number of larvae used and the mode of infection, i.e. whether single or trickle (multiple) exposure events (Rubio-Godoy and Tinsley, 2002). In contrast, development periods are known for a number of monopisthocotylean monogeneans.…”
Section: Discussionmentioning
confidence: 99%
“…to 4.5 for sexually mature parasites with 4 p.c. (Gannicott 1997, Rubio-Godoy andTinsley 2002). Intermediate values were assigned when new clamps had begun developing on the haptor, reflecting the addition of clamps as development proceeds.…”
Section: Methodsmentioning
confidence: 99%
“…in brown trout, Salmo trutta (L.), a native European host (Llewellyn 1956, Paling 1969, Slinn 1963. Experimental trickle and single infection of rainbow trout, Oncorhynchus mykiss (Walbaum), suggested that D. sagittata invades the gills passively with the respiratory current, and that developing worms migrate anteriorly post-invasion to, presumably, preferred gill arches (Rubio-Godoy and Tinsley 2002). In this study, I report the microhabitat preference of D. sagittata in farmed O. mykiss, an introduced species reared extensively in Europe.…”
mentioning
confidence: 99%
“…Parasite development was determined by counting the number of clamps present on the haptor; a mean developmental index (DI) was calculated for worms from individual fish, and mean DI are reported for each fish year-class (Rubio-Godoy & Tinsley 2002). DI values range from 1 for freshly attached worms with 1 pair of clamps, to 4.5 for sexually mature worms with 4 pairs of clamps.…”
Section: Materials and Methods Fishmentioning
confidence: 99%
“…This results in clear annual transmission cycles: no infections occur during the winter, while transmission is continuous during the summer and until late autumn. Knowledge of D. sagittata biology enabled the establishment of a dependable experimental infection system (Rubio-Godoy & Tinsley 2002). In laboratory trials, rainbow trout were partially protected against controlled challenges following immunisation with D. sagittata extracts, and a significant negative correlation was found between antibody levels and parasite numbers recovered from immunised fish (Rubio-Godoy et al 2003).…”
mentioning
confidence: 99%